Web-based access control system - Teixeira, A. (2011)
This article describes a web-based system to control and manage the access to the ESTCB, which it is under development as a student’s final project. Beyond an important pedagogical and technological value, we believe that this work is an important step towards offering strong and efficient security management for access control systems. We make use of standard technologies in use on the Web, to make an effective campus-wide security system. The system management and configuration, the consultation of access information for schedules, users, spaces, among others, will be carried out through the Internet. The proposed model is based on the use of two data nets: a CAN field bus to which are connected magnetic cards readers, door locks and sensors of each access place and the Ethernet that establishes connection between different CAN field bus and servers, which contain information about users and access rules.